2016
DOI: 10.1186/s40064-016-2352-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of organochlorine pesticide residues in soils and drinking water sources from cocoa farms in Ghana

Abstract: Residues of organochlorine pesticides were determined in soils and drinking water sources in cocoa growing areas in Ghana. Soil samples analysed showed the presence of four organochlorine pesticide residues namely lindane (0.005–0.05 mg/kg), beta-HCH (<0.01–0.05 mg/kg), dieldrin (0.005–0.02 mg/kg), and p,p′-DDT (0.005–0.04 mg/kg), with dieldrin occurring most frequently. Similarly, organochlorine pesticide residues detected in the water samples were lindane (0.01–0.03 µg/l), alpha-endosulfan (0.01–0.03 µg/l), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 38 publications
1
41
3
Order By: Relevance
“…The range of the percentage organic carbon content of the analyzed soil samples was higher than 0.44-0.9% reported by Bentum et al, [15], who considered the result of their findings, in the top soils of some cocoa growing areas in five districts of the central region of Ghana, to be very low. However, our values were lower than 0.8-6.12% and 1.54-10.6% reported for organic carbon and organic matter in soils from a cocoa farm in Ghana [14]. Table 4 shows that fifteen different pesticide residues were detected in the cocoa samples while Table 5 presents the results of the OCPs in the soil.…”
Section: Soil Physicochemical Propertiescontrasting
confidence: 61%
See 1 more Smart Citation
“…The range of the percentage organic carbon content of the analyzed soil samples was higher than 0.44-0.9% reported by Bentum et al, [15], who considered the result of their findings, in the top soils of some cocoa growing areas in five districts of the central region of Ghana, to be very low. However, our values were lower than 0.8-6.12% and 1.54-10.6% reported for organic carbon and organic matter in soils from a cocoa farm in Ghana [14]. Table 4 shows that fifteen different pesticide residues were detected in the cocoa samples while Table 5 presents the results of the OCPs in the soil.…”
Section: Soil Physicochemical Propertiescontrasting
confidence: 61%
“…The pH values in the various farms in our study were mostly acidic compared to 7.34-8.46 reported in four cocoa farms in Ghana [14]. The result of the percentage particle size composition of the soil samples showed that the soils were characterized by high sand contents with overall range of 68.84-73.58%, the clay composition ranged from 14.56% to 16.64% and the slit content of the soils were in the range 11.86% to 15.62%.…”
Section: Soil Physicochemical Propertiescontrasting
confidence: 55%
“…This difference is likely to be due the fact that DDT was banned in Thailand for almost 30 years, and also in Egypt but the potatoes are tuberous plants growing under the ground whereas the guava fruits are produced from a tree. It has been demonstrated that even when DDT was withdrawn from markets for a long time afterwards residues of DDT isomers and its metabolites are still frequently detected in the environmental regions such as soils, sediments and surface water (Fosu‐Mensah, Okoffo, Darko, & Gordon, ; Ma et al, ; Mansouri et al, ). In Thailand, DDT and its metabolites were scarcely detected in fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…It is indigenous to West Africa and mostly found within cocoa farms in South-western Nigeria. Insect pests and diseases pose a major challenge to the production of crop including cocoa, resulting in adverse consequences of the economy [7], particularly food insecurity.…”
Section: Introductionmentioning
confidence: 99%